Perbedaan Orientasi Keberagamaan Pada Santri Pondok Pesantren Modren Dan Siswa Sekolah Madrasah Aliyah Negeri - Pramesti, Diah Ayu, Drs. Soleh Amini, M.Si, Psi (2016)
This study aims to understand and describe the religious orientation of which is owned by a modern boarding school students and students madrasah aliyah country. This research was conducted in two places, namely MAN 1 Surakarta and boarding modren walisongo sragen. Research subjects in this study of 100 people with 50 students of MAN 1 and 50 boarding school students modren. Sampling was done by sampling rundom technique. The method used in this penlitian is a quantitative method by using religious orientation scale. This research data analysis techniques using independent sample t-tests. Based on the results of independent testing of samples t-test t-test values obtained at t = 1,539 with coefficient sig = 0.217 (p> 0.005) which means there is no difference in the religious orientation of boarding school students and students madrasah aliyah modren country. Subjects in this study had a religious orientation is very high.